Proceso de atención de enfermería en paciente preescolar con pielonefritis. - Bermeo Pazmiño, María Esther (2021)
An analysis of a clinical case was carried out with the objective of identifying the risk factors that influence the predisposition of urinary tract infections in preschool patients, and at the same time to publicize the nursing care in the care of pediatric patients with Acute pyelonephritis during hospitalization. The clinical case that was developed is of a 4-year-old female patient, born in the city of Ambato and residing in Quito, with a history of urinary tract infection. The girl's mother goes to the HGSFQ, she is treated in emergencies presenting fever of 38.5, diaphoresis, intense pain in the lumbar area, where she was evaluated and diagnosed with acute pyelonephritis. He enters the Pediatric area due to presenting a clinical picture of Pyelonephritis evaluated through laboratory tests, verifying altered patterns and vital signs that appear in altered ranges in the pediatric patient, resulting in the improvement of the patient's symptoms through evolution, evaluation of the present symptoms and the correct application of the NANDA NIC and NOC triad.